Long-Term Intracranial Progression-Free Survival in Lung Cancer Brain Metastases Extended Beyond 50 Months with Gubenxiaoyi Formula (GBXY): A Groundbreaking Case Study - Zhengzheng Yang; Haiming Li; Lei Chen; Shujiao Li; Dong Chen; Taicheng Lu; Tongjing Ding; Ruiyang Han; Peiyu Cheng; Xiaomin Wang (Integrative Cancer Therapies)
Background: The prevalence of brain metastases (BM) in lung cancer patients is notably high and is associated with poor prognoses. The efficacy of standard treatment regimens in improving intracranial progression-free survival (IPFS) for lung cancer BM is markedly limited. While traditional Chinese medicine (TCM) has been effective in enhancing the quality of life and prognosis of lung cancer patients, its efficacy in treating BM remains unreported. Case presentation Here, we present a case of a middle-aged female with lung cancer BM, whose condition was assessed as progressive post-standard treatment including two local surgeries (both involving resection of cerebellar space-occupying lesions), stereotactic radiotherapy, chemotherapy and EGFR-TKIs. Subsequently, she underwent treatment with the traditional Chinese herbal formula gubenxiaoyi (GBXY). The patient was treated with GBXY for a total duration of 55 months. After treatment, a significant reduction of about 50% in intracranial lesions was observed, accompanied by an extension of both Intracranial Progression-Free Survival (IPFS) and Cognitive Deterioration-Free Survival (CDFS) exceeding 50 months. Conclusion These results demonstrate that in patients with lung cancer brain metastases (BM) unresponsive to standard treatments, GBXY not only has the potential to effectively prolong IPFS and decelerate cognitive decline, but may also contribute to a reduction in intracranial tumor burden. This suggests that GBXY could be a promising therapeutic option that warrants further investigation.